Control of Globally Invasive Common Carp: An 11‐Year Commercial Trial of the Williams' Cage. (25th September 2018) - Stuart, Ivor G.; Conallin, Anthony J.
Abstract: The Common Carp Cyprinus carpio is a major pest fish in Australia, North America, New Zealand, and parts of Europe. The Williams' carp separation cage was developed to separate Common Carp from native fish as they pass through fishways by exploiting their strong migratory and unique jumping behaviors. We report on an 11‐year commercial application of the Williams' cage at Lock 1 on the lower Murray River (southeast Australia), where a high biomass of Common Carp resides. Between November 2007 and January 2018, the cage was operated by a collaborative team of river managers, weir keepers, commercial fishers, and researchers. To date, approximately 723 metric tons of adult Common Carp (~289, 431 fish) have been captured at a maximum rate of 5 metric tons/d. These fish were marketed for a total return of over AU$0.90 million, far exceeding setup costs. Catches and separation efficiencies were highest in austral spring, when fish were migrating to spawn, and bycatch of nontarget native fish was practically zero (0.03%). Population modeling indicated that a combination of commercial carp fishing, low inflows, and the Williams' cage has caused a significant reduction in Common Carp numbers in the lower Murray River. The Williams' cage has now successfully moved from an experimental idea to full commercial viability, and at Lock 1 it is playing a valuable role in controlling the dispersal and abundance of globally invasive Common Carp.